Analytical model of dislocation nucleation on a near-surface void under tensile surface stress - Pohjonen, A; Djurabekova, F; Kuronen, A; Fitzgerald, S; Nordlund, K (2012)
We have analyzed in detail the mechanism leading to tip growth on a surface which operates via nucleation of dislocations on a near-surface void under tensile surface stress. We derived a simplified analytical model describing the relevant physical factors related to the observed linearity between the void radius and the maximum depth of the void for the growth to occur. The model is based on the direct numerical calculation of atomic level stresses in the simulated system. Based on the present model we can estimate this maximum depth for a void of a certain size under a given stress in the size range which is beyond the feasibility of the molecular dynamics simulation method. © 2012 Copyright Taylor and Francis Group, LLC.